Functional chimeras of flagellar stator proteins between E. coli MotB and Vibrio PomB at the periplasmic region in Vibrio or E. coli. Issue 2 (29th January 2015) - Nishino, Yuuki; Onoue, Yasuhiro; Kojima, Seiji; Homma, Michio
Abstract The bacterial flagellar motor has a stator and a rotor. The stator is composed of two membrane proteins, MotA and MotB in Escherichia coli and PomA and PomB in Vibrio alginolyticus. The Vibrio motor has a unique structure, the T ring, which is composed of MotX and MotY. Based on the structural information of PomB and MotB, we constructed three chimeric proteins between PomB and MotB, named PotB91, PotB129, and PotB138, with various chimeric junctions. When those chimeric proteins were produced with PomA in a ΔmotAB strain of E. coli or in ΔpomAB and ΔpomAB ΔmotX strains of Vibrio, all chimeras were functional in E. coli or Vibrio, either with or without the T ring, although the motilities were very weak in E. coli. Furthermore, we could isolate some suppressors in E. coli and identified the mutation sites on PomA or the chimeric B subunit. The weak function of chimeric PotBs in E. coli is derived mainly from the defect in the rotational switching of the flagellar motor. In addition, comparing the motilities of chimera strains in ΔpomAB, PotB138 had the highest motility. The difference between the origin of the α1 and α2 helices, E. coli MotB or Vibro PomB, seems to be important for motility in E. coli and especially in Vibrio.